Enhancing CO2/N2 and CO2/CH4 Separation Properties of PES/SAPO-34 Membranes Using Choline Chloride-Based Deep Eutectic Solvents as Additives - Jonathan S. Cardoso; Zhi Lin; Paulo Brito; Licínio M. Gando-Ferreira (Membranes)
CO2 separation is an important environmental method mainly used in reducing CO2 emissions to mitigate anthropogenic climate change. The use of mixed-matrix membranes (MMMs) arrives as a possible answer, combining the high selectivity of inorganic membranes with high permeability of organic membranes. However, the combination of these materials is challenging due to their opposing nature, leading to poor interactions between polymeric matrix and inorganic fillers. Many additives have been tested to reduce interfacial voids, some of which showed potential in dealing with compatibility problems, but most of them lack further studies and optimization. Deep eutectic solvents (DESs) have emerged as IL substitutes since they are cheaper and environmentally friendly. Choline chloride-based deep eutectic solvents were studied as additives in polyethersulfone (PES)/SAPO-34 membranes to improve CO2 permeability and CO2/N2 and CO2/CH4 selectivity. SAPO-34 crystals of 150 nm with a high surface area and microporosity were synthesized using dry-gel methodology. The PES/SAPO-34 membranes were optimized following previous work and used in a defined composition, using 5 or 10 w/w% of DES during membrane preparation. All MMMs were characterized by their ideal gas permeability using N2 and CO2 pure gasses. Selected membranes were also tested using CH4 pure gas. The results presented that 5 w/w%, in polymer mass, of ChCl–glycerol presented the best result over the synthesized membranes. An increase of 200% in CO2 permeability maintains the CO2/N2 selectivity for the non-modified PES/SAPO-34 membrane. A CO2/CH4 selectivity of 89.7 was obtained in PES/SAPO-34/ChCl-glycerol membranes containing 5 w/w% of this DES, which is an outstanding ideal separation performance for MMMs when compared to other results in the literature. FTIR analysis reiterates the presence of glycerol in the membranes prepared. Dynamic Mechanical Thermal Analysis (DMTA) shows that the addition of 5 w/w% of DES does not impact the membrane flexibility or polymer structure. However, in concentrations higher than 10 w/w%, the inclusion of DES could lead to high membrane rigidification without impacting the overall thermal resistance. SEM analysis of DES-enhanced membranes presented asymmetric final membranes and reaffirmed the results obtained in DMTA about rigidified structures and lower zeolite–polymer interaction with higher concentrations of DES.